Preparing a Personalized Meal by Using Soy, Cricket, and Egg Albumin Protein Based on 3D Printing - Farnaz Mirazimi; Jordi Saldo; Francesc Sepulcre; Alvar Gràcia; Montserrat Pujolà (Foods, 2022)
Recently, personalized meals and customized food design by means of 3D printing technology have been considered over traditional food manufacturing methods. This study examined the effects of different proteins (soy, cricket, and egg albumin protein) in two concentrations (3% and 5%) on rheological, textural, and 3D printing characteristics. The textural and microstructural properties of different formulations were evaluated and compared. The addition of soy and cricket protein induced an increase in yield stress (τ₀), storage modulus (G′), and loss modulus (G″) while egg albumin protein decreased these parameters. The textural analysis (back extrusion and force of extrusion) demonstrated the relationship between increasing the amount of protein in the formula with an improvement in consistency and index of viscosity. These values showed a straight correlation with the printability of fortified formulas. 3D printing of the different formulas revealed that soy and cricket proteins allow the targeting of complex geometry with multilayers.